2017
DOI: 10.1002/smll.201603893
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Modified Graphitic Carbon Nitride Nanostructures as an Efficient Electrocatalyst for Water Oxidation

Abstract: There is an urgent need to develop metal-free, low cost, durable, and highly efficient catalysts for industrially important oxygen evolution reactions. Inspired by natural geodes, unique melamine nanogeodes are successfully synthesized using hydrothermal process. Sulfur-modified graphitic carbon nitride (S-modified g-CN ) electrocatalysts are obtained by annealing these melamine nanogeodes in situ with sulfur. The sulfur modification in the g-CN structure leads to excellent oxygen evolution reaction activity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 74 publications
4
39
3
Order By: Relevance
“…Sulfur-modified g-C 3 N 4 , reported by Kale et al [3], has shown excellent catalytic properties due to minimization of the activation energy for the OER. Inspired by melamine nanogeodes (MNG), the group synthesized the g-C 3 N 4 nanostructure from MNG powder, which was obtained through a simple hydrothermal process with melamine.…”
Section: Graphitic Carbon Nitridementioning
confidence: 99%
See 2 more Smart Citations
“…Sulfur-modified g-C 3 N 4 , reported by Kale et al [3], has shown excellent catalytic properties due to minimization of the activation energy for the OER. Inspired by melamine nanogeodes (MNG), the group synthesized the g-C 3 N 4 nanostructure from MNG powder, which was obtained through a simple hydrothermal process with melamine.…”
Section: Graphitic Carbon Nitridementioning
confidence: 99%
“…Water electrolysis, an efficient and clean technology used for the generation of high-purity hydrogen, also shows excellent adaptability. Solar-powered water splitting systems are developed through the engagement of photocatalytic and photoelectrochemical systems that effectively convert incident solar energy into chemical bonds by using light-absorbing materials [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, heteroatom doping can enhance the surface, electronic, and catalytic properties of carbon nanomaterials via charge redistribution and/or formation of new energy states . The doping, substitution, modification, or combination of heteroatoms such as N, B, S, and P, in carbon nanomaterials have been extensively studied for many important energy‐related applications. In particular, codoping, i.e., doping with more than one type of heteroatom, can impart synergistic effects and improved performance compared to materials doped with only a single kind of heteroatom .…”
Section: Introductionmentioning
confidence: 99%
“…The water splitting system gives the impression to be a sensational renewable and clean energy resources to replace the use of limited fossil fuels . The water splitting systems are strongly dependent on the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER),, where the operational efficiencies of OER and HER reactions are explicitly dependent on their catalysts. Ruthenium or iridium‐based noble metals are being used as effective electrocatalysts for OER and noble platinum‐based electrodes are involved for HER catalysts .…”
Section: Introductionmentioning
confidence: 99%